The magnetic cooling of YTiO3 compound for magnetic refrigeration. (1st February 2022) - Arejdal, M.; Bahmad, L.; Ez-zahraouy, H.
Abstract: We theoretically conducted a study on the magnetic behaviors and magneto-caloric performance of the YTiO3 compound, a studied system in this research paper. In accordance with the main objective if this paper, we restricted our research to only studying a number of the system-related elements such as the magnetization M(T), the inverse magnetization M −1 (T), the isothermal magnetic hysteresis loop (M − H), the magnetic entropy change (ΔSM ), the relative cooling power (RCP) and the refrigerant capacity (RC). By so doing, we reached a number of results as: the inverse magnetization M −1 ( T ), showed that the Curie temperature ( T c ) of the YTiO3 compound was 26.5 K; the largest of the hysteresis loop H(M) at low temperatures indicates that the YTiO3 compound belongs to hard magnetic materials; and at H = 5T, the maximum values of the magneto-caloric effect (MCE), which were represented by the magnetic entropy change (ΔSM ), the relative cooling power (RCP), and the refrigerant capacity (RC), were found to be 1.91 J/kg K and 11.45 J/kg and 8.59 J/kg, respectively. Highlights: The YTiO3 has been studied. Thermal magnetization, Inverse magnetization of the system have been established. Transition temperature has been deduced. Isothermal magnetic entropy change, relative cooling power (RCP) and RC have been examined.